Absent in melanoma 2 inflammasome is required for host defence against Streptococcus pneumoniae infection - Feng, Siwei (Innate Immun, 2019)
Streptococcus pneumoniae, a leading cause of invasive pneumococcal disease, is responsible for high mortality and morbidity worldwide. A previous study showed that the NLR family pyrin domain containing 3 (NLRP3) and absent in melanoma 2 (AIM2) inflammasomes are essential for caspase-1 activation and IL-1β production in the host response to S. pneumoniae infection. The function of NLRP3 in host innate immunity to S. pneumoniae was studied in vivo and in vitro. However, the role of AIM2 in host defence against S. pneumoniae remains unclear. Here, we show that AIM2-deficient (AIM2(–/–)) mice display increased susceptibility to intra-nasal infection with S. pneumoniae in comparison to wild type mice and that this susceptibility was associated with defective IL-1β production. Macrophages from AIM2(–/–) mice infected with S. pneumoniae showed impaired secretion of IL-1β as well as activation of the inflammasome, as determined by the oligomerisation of apoptosis-associated speck-like protein containing a CARD (ASC) and caspase-1 activation. Taken together, these results indicate that the AIM2 inflammasome is essential for caspase-1-dependent cytokine IL-1β production and eventual protection from pneumococcal infection in mice.